EXPERIMENTAL AQUEOUS ALTERATION OF THE ALLENDE METEORITE UNDER OXIDIZING CONDITIONS: CONSTRAINTS ON ASTEROIDAL ALTERATION - Jones C.L.; Brearley A.J. (My University, 2006)
We have performed an experimental study of the aqueous alteration of the Allende CV3 carbonaceous chondrite under highly oxidizing conditions, in order to examine the alteration behavior of Allende’s anhydrous mineralogy. The experiments were carried out at temperatures of 100, 150, and 200 °C, for time periods between 7 and 180 days, with water/ rock ratios ranging from 1:1 to 9:1. Uncrushed cubes of Allende were used so that the spatial relationships between reactant and product phases could be examined in detail. Scanning electron microscope studies show that in all the experiments, even those of short duration (7 days), soluble salts of Ca and Mg (CaSO4, CaCO3, and MgSO4) precipitated on the sample surface, indicating that these elements are rapidly mobilized during alteration. In addition, iron oxides and hydroxides formed on the sample surfaces. The sulfates, carbonates, and the majority of the iron-bearing secondary minerals are randomly distributed over the surface of samples. In some instances the iron oxides and hydroxides are constrained to the boundaries of altering mineral grains. Transmission electron microscope studies show that the FeO-rich olivine in the interior of the samples has altered to form interlayered serpentine/saponite and Fe-oxyhydroxides. The degree of alteration increases significantly with increasing water/rock ratio, and to a lesser extent with increasing duration of heating. The serpentine/ saponite forms both by direct replacement of the olivine in crystallographically oriented intergrowths, and by recrystallization of an amorphous Si-rich phase that precipitates in pore space between the olivine grains. The alteration assemblage bears many similarities to those found in altered carbonaceous chondrites, although in detail there are important differences, which we attribute to (a) the relatively high temperatures of our experiments and (b) comparatively short reaction times compared with the natural examples. In terms of mineral assemblage, our experiments most closely resemble alteration in the CI chondrites, although the degree of alteration of our experiments is much lower. CI chondrites contain serpentine/saponite intergrowths and veins of Ca-sulfate and Ca-carbonate as well as the Fe-oxyhydroxide, ferrihydrite. However, the phyllosilicate phases formed in our experiments are somewhat coarser-grained than the finest phyllosilicate fraction present in CI chondrites, suggesting that alteration of the CI chondrites occurred at lower temperatures. In terms of mineral assemblage, our experiments also appear to come close to matching CR chondrites, although we infer that CR alteration probably occurred at temperatures <100 °C, based on the very fine-grained size of phyllosilicates in CR matrices. ? 2005 Elsevier Inc. All rights reserved.
Keywords: ALLENDE METEORITE; METEORITE; MINERAL ALTERATION